Are characteristics of metropolis matters for structural transformation of provinces: A spatial approach in the case of Vietnam - Truong Cong Bac; Van Tran; Tran Thanh Long (Cogent Social Sciences)
This study analyzes the impact of metropolises on the structural transformation of provinces based on specific metropolises’ characteristics. Moran I index on the share of non-agricultural sectors in the economic structure is firstly employed to examine the spatial autocorrelation between provinces in Vietnam. Furthermore, the relationship between metropolises and the change in the economic structure of provinces is analyzed quantitatively using spatial panel data models based on data from the statistics yearbook of all 63 areas in the period 2015 to 2018. The research results confirm the role of metropolises in the process of structural transformation of the provinces. Provinces with a high proportion of non-agricultural sectors in the economic structure show the concentration around metropolises. The destination for migration, the origin of remittance, and the market for neighboring provinces, are the function of metropolises. These roles are seen as driving forces for off-farm activity through changes in the incomes of neighboring provinces. Accordingly, focusing on specific metropolises characteristics as well as enhancing regional connectivity will contribute to promoting effective provincial structural transformation.